Endogenous P loss in sheep fed with different P levels - Louvandini, Helder; Vitti, Dorinha Miriam Silber Schmidt (Pesquisa Agropecuaria Brasileira, 1994)
The aim of this study was to investigate the effects of different P levels (0, 1, 2 and 3g/d) on endogenous fecal P and to evaluate the minimum P requeriment for sheep. Sixteen castrated sheep, with mean live weight of 40 kg were kept in metabolic cages receiving a semipurified diet and bone meal as P supplement. At the 21 st day, through jugular vein, 200mCi P-32 were injected in each animal, feces and blood samples being collected during 8 days for endogenous P determination. P absorption, total output and endogenous P were related to P supplied. Mean daily endogenous fecal and urinary output was 10.65 and 0.1 mg/kg live weight, with an average absorption coefficient of 80%. The daily requeriment for maintenance was 13.44 mg/ kg of live weight.